Thyroid hormones modifications among COVID-19 patients undergoing pulmonary rehabilitation - Croce, Laura; Zampogna, Elisabetta; Coperchini, Francesca; Costa, Pietro; Pignatti, Patrizia; Visca, Dina; Spanevello, Antonio; Rotondi, Mario (Frontiers in Endocrinology, 2023)
Introduction: patients with severe COVID-19 often experience long-lasting disabilities that can improve after pulmonary rehabilitation. Moreover patients with severe COVID-19 display thyroid function alterations due to a non-thyroidal illness syndrome (NTIS). The aim of our study was to evaluate thyroid function parameters among patients hospitalized for COVID-19 who were eligible or not to respiratory rehabilitation and their modifications during follow-up. Materials and Methods: post-COVID-19 patients referred to a Respiratory Rehabilitation Unit were evaluated. Outpatients, not candidate for rehabilitation, were enrolled as Control group. Patients who had completed a 4-week-rehabilitation program were enrolled as Rehabilitation Group. All patients were evaluated at T0 (4 weeks after the discharge home in Control Group and after completion of rehabilitation in Rehabilitation Group) and at T1 (3 months after T0). Results: The final study group included 39 patients (20 in the Rehabilitation group and 19 in the Control group). Patients in the Rehabilitation Group had more frequently received invasive or non-invasive ventilation, had a longer length-of-stay in referring hospitals, had a higher number of comorbidities and displayed a worse performance at 6-minute-walking-test (6MWT) and Short-Physical-Performance-Battery-test (SPPB). FT3 values were lower at T0 in the Rehabilitation Group, while TSH and FT4 values were similar in the two groups. While no significant modifications in thyroid-function-parameters were observed in the Control Group, a significant increase in FT3 value was observed in the Rehabilitation Group at T1. Participants of both groups had improved the results of 6MWT at T1, while SPPB values improved only in the Rehabilitation Group. Conclusions: COVID-19 patients after pulmonary rehabilitation experience an increase in FT3 values during follow-up, paralleled with an amelioration of functional capabilities.